Amide proton transfer-weighted imaging and T1 mapping as diagnostic tools to evaluate high-risk histopathologic phenotypes before surgery in rectal adenocarcinoma and their correlation with Ki-67 expression:a two-center study - Yaxin Chai; Yaxin Chai; Yongchao Niu; Ruixue Cheng; Pan Liang; Jianbo Gao (Frontiers in Oncology)
ObjectivesTo investigate the application of amide proton transfer (APT)-weighted MRI, T1 mapping in evaluating the preoperative high-risk histopathologic phenotypes of rectal adenocarcinoma and their correlation with Ki-67 expression.Materials and MethodsRetrospective collection of 178 confirmed cases of rectal adenocarcinoma from two centers (center 1: 97 cases, center 2: 81 cases). High-resolution T2WI, APT, T1 mapping, diffusion-weighted imaging (DWI), and Ki-67 staining were performed in all patients. The measured parameters included APT signal intensity (APT SI), T1 relaxation time before (native T1) and after (post-contrast T1) enhancement, and apparent diffusion coefficient (ADC). The receiver operating characteristic (ROC) curve was used to evaluate diagnostic efficiency, and Spearman correlation analysis was used to evaluate the correlation between parameters with Ki-67, respectively.ResultsAPT SI values were significantly different between the mucinous adenocarcinoma (MC) group and the common adenocarcinoma (AC) group in two centers (center 1: [2.64 ± 0.33%] vs. [2.22 ± 0.78%], P<0.05), (center 2: [3.27 ± 0.80%] vs. [2.59 ± 0.77%], P<0.05). In the AC group, APT SI, native T1 and ADC values were significantly different between T1–2 and T3–4 groups (center 1: [2.58 ± 0.69%] vs. [1.61 ± 0.49%], [1540 ± 150 ms] vs. [1360 ± 130 ms], [0.85 ± 0.15×10-3 mm2/s] vs. [0.99± 0.15×10-3 mm2/s], respectively, all P<0.05), the results were consistent with the findings of center 2. APT SI and native T1 values in the lymph node metastasis group were higher than those in the non-metastatic group (center 1: [2.49 ± 0.77%] vs. [2.07 ± 0.74%], [1540 ± 170 ms] vs. [1430 ± 160 ms], respectively, all P<0.05), the result were consistent with the findings of center 2. APT SI were statistically significant in evaluating lymphovascular invasion (LVI) and extramural vascular invasion (EMVI) in two centers (P<0.05). Ki-67 expression was correlated with APT SI (mild to medium), ADC (mild) and native T1 (mild to high) in two centers, respectively (P<0.05), but there was no correlation between post-contrast T1 and Ki-67 (P>0.05).ConclusionAPT and T1 mapping can be used to evaluate the preoperative pathological classification, TN staging, and structural invasion of rectal adenocarcinoma, which has the potential to become an imaging marker for the evaluation of high-risk histopathologic phenotypes and Ki-67 expression of rectal adenocarcinoma.